ANGGARAN OPERASIONAL SEBAGAI ALAT PENGENDALIAN MANAJEMEN PADA PDAM TIRTA TUAH BENUA KUTAI TIMUR - Sudriana, Meylinda (EKONOMIA, 2014)
MEYLINDA SUDRIANA , Faculty of Economics, University of Samarinda August 17, 1945 , Operating Budget as a Tool Management Control In PDAM Tirta Tuah Continent East Kutai . Under the guidance of Mrs. and Mrs. Ida Titin Ruliani Rahmawati.PDAM Tirta Tuah Continent East Kutai is a locally-owned company that works to meet the water needs in the region Sengatta , East Kutai . In carrying out its role as an organization , PDAM has financial planning for the future are summarized in a budget . The problem formulation which can be authors point of this study were ( 1 ) Was there a deviation between the operating budget and its realization on PDAM Tirta Tuah East Kutai Continents ( 2 ) What causes the operating budget deviations PDAM Tirta Tuah Continent East Kutai.Basic theory used in this study is that nsuatu budget plan systematically arranged in the form of figures and expressed in monetary units , including the company's activities for a certain period in the future . Hypotheses that could be addressed are ( 1 ) An operational deviations between budget and actual on the Continent taps Titra Tuah East Kutai ( 2 ) The cause of the deviation on the Continent PDAM Tirta Tuah East Kutai . Analysis tools used in hypothesis testing is the analysis of variance , comparison between the budget and the deviation formula and data processing tools Microsoft Excel 2007.